-(5x-2y+7z)=

Simple and best practice solution for -(5x-2y+7z)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(5x-2y+7z)= equation:


Simplifying
-1(5x + -2y + 7z) = 0
(5x * -1 + -2y * -1 + 7z * -1) = 0
(-5x + 2y + -7z) = 0

Solving
-5x + 2y + -7z = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2y' to each side of the equation.
-5x + 2y + -2y + -7z = 0 + -2y

Combine like terms: 2y + -2y = 0
-5x + 0 + -7z = 0 + -2y
-5x + -7z = 0 + -2y
Remove the zero:
-5x + -7z = -2y

Add '7z' to each side of the equation.
-5x + -7z + 7z = -2y + 7z

Combine like terms: -7z + 7z = 0
-5x + 0 = -2y + 7z
-5x = -2y + 7z

Divide each side by '-5'.
x = 0.4y + -1.4z

Simplifying
x = 0.4y + -1.4z

See similar equations:

| 3*5+2=4*5-3 | | 4=ts+3.75 | | X+3*9=63 | | 4=t+3.75s | | X=10(140-70)+40 | | 3*-5+2=4*-5-3 | | 50q=350 | | 3t-9r+3(2r+5t)= | | (-8x+2)+(-5x+7)= | | X=4s+3.75 | | 1-6n=-7n-7 | | 4b(b+9)-12b= | | 5x+11=3x+32 | | 5(3x+5)=5(5x+1) | | 4x^4+5x^2=0 | | 4-x=10x | | X=4+3.75s | | (x-7)+43=180 | | 3(X+8)+4=7x-4(X-3) | | (2x-4)+(-x+9)= | | 3x+9=7x+19 | | 221-6x=-11-14x | | 3x+9=19x+7 | | 4/5b-3=9/10b+2 | | 3t-9r+6r+15t= | | 9x+2=3y | | 3(X+4)=6x+2-3x+10 | | x+(-10)= | | 152=4x+3(7x-16) | | -5m-15+6m+2=15-8 | | 57-4x=-6x+65 | | (x+2)(x+3)=x*x-10 |

Equations solver categories